Functional MRI Studies in Friedreich's Ataxia: A Systematic Review - Vavla, Marinela; Arrigoni, Filippo; Peruzzo, Denis; Montanaro, Domenico; Frijia, Francesca; Pizzighello, Silvia; De Luca, Alberto; Della Libera, Emma; Tessarotto, Federica; Guerra, Paola; Harding, Ian H.; Martinuzzi, Andrea (Frontiers in Neurology, 2022)
Friedreich’s ataxia (FRDA) is an inherited neurodegenerative movement disorder with early onset, widespread cerebral and cerebellar pathology, and no cure available so far. Functional MRI (fMRI) studies, although currently limited in number, have provided a better understanding of brain changes in people with FRDA. This systematic review aimed to provide a critical overview of the findings and methodologies of all fMRI studies conducted in genetically confirmed FRDA so far, and to offer recommendations for future study designs. Twelve cross-sectional and longitudinal fMRI studies, including a total of 198 FRDA children and young adult patients and 205 healthy controls (HC), were analyzed according to the inclusion criteria. Details regarding GAA triplet expansion, demographic and clinical severity measures were widely reported. fMRI designs included motor and cognitive task paradigms, and resting-state studies, with widespread changes in functionally activated areas and extensive variation in study methodologies. These studies highlight a mixed picture of both hypo- and hyperactivations in different cerebral and cerebellar brain regions depending on fMRI design and cohort characteristics. Functional changes often correlate with clinical variables. In aggregate, the findings provide support for cerebro-cerebellar loop damage and the compensatory mechanisms hypothesis. Current literature indicates that fMRI is a valuable tool for gaining in vivo insights into FRDA pathology, but addressing key limitations will be key to improving the design, interpretation, and generalizability of studies in the future.